Adherence to the Canadian 24-hour movement guidelines and vision impairment in children and adolescents: a cross-sectional study - Haoxi Zhong; Huimin Zhu; Mingjie Jiang; Jingfeng Mu (Frontiers in Medicine)
ObjectivesTo investigate the associations between adherence to the Canadian 24-hour movement guidelines—covering physical activity (PA), screen time (ST), and sleep duration (SD)—and vision impairment, specifically myopia and myopic anisometropia, among children and adolescents in Shenzhen, China.MethodsA cross-sectional study was conducted in 2022 with 4,649 participants. Adherence to the guidelines was assessed using self-reported PA, ST, and SD measures, while vision impairment was clinically evaluated. Logistic regression models were used to analyze the associations, adjusting for sociodemographic factors.ResultsAmong the participants, 48.63% were diagnosed with myopia and 11.01% had myopic anisometropia. Meeting the ST guideline was associated with a reduced risk of myopia (aOR = 0.86, 95% CI = 0.76-0.98) and myopic anisometropia (aOR = 0.78, 95% CI = 0.64-0.95). Meeting both PA and ST guidelines further reduced the odds of myopia (aOR = 0.73, 95% CI = 0.56-0.97) and myopic anisometropia (aOR = 0.60, 95% CI = 0.41-0.89). Meeting all three guidelines (PA, ST, and SD) significantly reduced the odds of myopia (aOR = 0.71, 95% CI: 0.53–0.93) and showed a trend toward reduced risk of anisometropia (aOR = 0.69, 95% CI: 0.47–1.02), compared to those who met none. Meeting two guidelines also significantly reduced the risk of myopia (aOR = 0.76, 95% CI: 0.59–0.97) and anisometropia (aOR = 0.71, 95% CI: 0.51–1.00).ConclusionAdherence to the 24-hour movement guidelines, particularly meeting the ST and PA recommendations, was associated with a lower risk of myopia and myopic anisometropia. These findings highlight the importance of promoting balanced lifestyle behaviors, such as limiting screen time and encouraging physical activity, to mitigate vision impairment among children and adolescents.